Performance analysis and prediction using circuit model in a microstrip patch array - Soh, Ping Jack; Azremi, Abdullah Al Hadi; Dayang Khadijah, Hamzah; Raha, Abdul Rahim; Mohd Taufik, Jusoh; Junita, Mohd Nordin; R. Badlishah, Ahmad (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org